The Argentine Approach to Radiation Safety: Its Ethical Basis - Abel J. González (Science and Technology of Nuclear Installations)
The ethical bases of Argentina's radiation safety approach are reviewed. The applied principles are those recommended and established internationally, namely: the principle of justification of decisions that alters the radiation exposure situation; the principle of optimization of protection and safety; the principle of individual protection for restricting possible inequitable outcomes of optimized safety; and the implicit principle of intergenerational prudence for protection future generations and the habitat. The principles are compared vis-à-vis the prevalent ethical doctrines: justification vis-à-vis teleology; optimization vis-à-vis utilitarianism; individual protection vis-à-vis deontology; and, intergenerational prudence vis-à-vis aretaicism (or virtuosity). The application of the principles and their ethics in Argentina is analysed. These principles are applied to ALL exposure to radiation harm; namely, to exposures to actual doses and to exposures to actual risk and potential doses, including those related to the safety of nuclear installations, and they are harmonized and applied in conjunction. It is concluded that building a bridge among all available ethical doctrines and applying it to radiation safety against actual doses and actual risk and potential doses is at the roots of the successful nuclear regulatory experience in Argentina.